2018
DOI: 10.1055/a-0743-5259
|View full text |Cite
|
Sign up to set email alerts
|

Evidenzbasierte Behandlung von schwer psychisch kranken Menschen mit psychosozialen Therapien – Erstes Update der DGPPN-S3-Leitlinie erscheint Ende 2018

Abstract: Zusammenfassung Einleitung Schwere psychische Erkrankungen sind mit besonderen Belastungen und Risiken für die Betroffenen und deren Angehörige verbunden. Psychosoziale Therapien sind eine zentrale Säule der Behandlung. Material & Methoden Im Update der S3-Leitlinie „Psychosoziale Therapien bei schweren psychischen Erkrankungen“ werden auf der Basis aktueller wissenschaftlicher Evidenz und strukturierter Konsensfindung in einem repräsentativen Leitliniengremium umfassende Empfehlungen zur psychosozialen Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…In contrast, other models, such as the Individual Placement and Support model, directly incorporates the person with SMD into a job, receiving the necessary support within the job itself. This model has been shown to be more effective in achieving employment than the use of volunteerism as pre-vocational skills training or classical vocational rehabilitation [33,34]. These results have also been described in long-term unemployed people among the general population, where it has been identified that volunteering is not an adequate means for obtaining employment, although it does lead to greater self-respect and self-esteem [35].…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, other models, such as the Individual Placement and Support model, directly incorporates the person with SMD into a job, receiving the necessary support within the job itself. This model has been shown to be more effective in achieving employment than the use of volunteerism as pre-vocational skills training or classical vocational rehabilitation [33,34]. These results have also been described in long-term unemployed people among the general population, where it has been identified that volunteering is not an adequate means for obtaining employment, although it does lead to greater self-respect and self-esteem [35].…”
Section: Discussionmentioning
confidence: 93%
“…Im Rahmen der Peer-Begleitung nutzen sie diese wertvolle Erfahrung, um andere Menschen mit psychischer Erkrankung zu unterstützen. Peer-Begleitung ist eine international anerkannte, auch in Deutschland leitliniengestützte Intervention 1 2 3 4 . Die erfolgreiche Implementierung von Peer-Begleitung ist anspruchsvoll, da sie seitens der implementierenden Einrichtungen Veränderungen von konkreten Abläufen, sowie der Organisationskultur im Allgemeinen, notwendig macht 5 6 .…”
Section: Introductionunclassified